Recurrent spontaneous small bowel perforations with a rare pathology: non-familial visceral myopathy. Issue 5 (13th May 2021) - Shi, Meiyi; Choi, Young Mee; Kiselak, Elizabeth
Abstract : Visceral myopathy is a rare, often misdiagnosed disease characterised by abnormalities in the gastrointestinal smooth muscle layer. Its clinical presentation includes pseudo-obstruction, intestinal dysmotility and spontaneous perforation. We report an atypical case of a 51-year-old man with a history of recurrent small bowel perforations who presented with an acute abdomen. A laparotomy was performed with identification of a distal jejunal perforation. A small bowel resection with end-to-end anastomosis was done. Minimal adhesions were seen intraoperatively despite the patient's multiple prior surgeries. Pathology showed histiocytic inflammation and patchy loss of the muscle layer reflective of visceral myopathy. Genetic testing revealed a variant of uncertain significance in the myosin light chain kinase gene. It is difficult to make a conclusive diagnosis given the patient's clinical presentation closely mimicking other gastrointestinal disorders. However, it is crucial to consider visceral myopathy in patients with recurrent spontaneous intestinal perforations as a differential diagnosis.